Der Freischütz - Kozub, Ernst 1924-1971; Frick, Gottlob 1906-1994; Grundheber, Franz 1937-; Blankenheim, Toni 1921-2012; Saunders, Arlene 1930-2020; Mathis, Edith 1938-2025; Krause, Tom 1934-2013; Sotin, Hans 1939-; Minetti, Bernhard 1905-1998; Ludwig, Leopold 1908-1979 (Arthaus-Musik, 2006)
Max the Huntsman struggles against his rival Kaspar to win Agathe in marriage. His desperation leads him to bargain with the Devil in order to best Kaspar for the hand of his beloved.
Interpr.: Ernst Kozub, Max. Gottlob Frick, Kaspar. Franz Grundheber, Kilian. Toni Blankenheim, Cuno. Arlene Saunders, Agathe. Edith Mathis, Annchen. Tom Krause, Prine Ottokar. Hans Sotin, a hermit. Bernhard Minetti, Samiel. The Chorus of the Hamburg State Opera. The Ballet of the Hamburg State Opera. The Hamburg Philharmonic State Orchestra. Conducted by Leopold Ludwig. - Aufn.: Hamburg, Staatsoper, 1968. - Prod. by Polyphon Film- und Fernsehges. for NDR
Keywords: Opéras - Adaptations cinématographiques et télévisées; Operas; DVD-Video; Filmed operas